Household Budget and Calorie Consumption of Livestock Products: Evidence from Indonesia - Muzayyanah, Mujtahidah Anggriani Ummul Muzayyanah (2013)
This study intends to capture the household budget of livestock products consumption and its calorie consume in six provinces of Java Island in Indonesia. An empirical analysis is made by employing simple Engel model and the descriptive analysis. The result suggested that both household in urban and rural area spent their income for meat higher than that of egg and milk. In other words, as income increase consumption of meat responds much faster than consumption on egg and milk. The calorie consume from meat, egg and milk consumption are still low, under government’s recommendation.